The impact of smart contracts on banking efficiency and tokenization in financial markets in Iceland - Sverrir Haukur Gíslason 2001-; Thelma Kristín Tómasdóttir 2002- (2024)
This thesis explores the impact of smart contracts on banking efficiency and tokenization in financial markets in Iceland. It delves into the potential benefits of smart contracts and tokenization in enhancing financial processes and market operations. The research findings reveal that smart contracts and tokenization offer significant advantages in terms of efficiency and transparency in financial transactions. However, despite these potential benefits Iceland may not be among the first to fully implement these technologies due to various challenges, such as infrastructure constraints and cost considerations. Iceland’s financial system is also relatively efficient due to its small size and low volume enabling rapid and streamlined transactions. Unlike larger countries where transfers can be delayed, Iceland’s integrated banking and widespread use of digital payment solutions ensure quick and seamless transactions.